Post-malthusian dynamics in pre-industrial Scandinavia - Marc Klemp; Niels Framroze Møller (Brown University, Department of Economics, 2013)
Theories of economic growth hypothesize that the transition from pre-industrial stagnation to sustained growth is associated with a post-Malthusian phase in which technological progress raises income and spurs population growth while offsetting diminishing returns to labour. Evidence suggests that England was characterized by post-Malthusian dynamics preceding the Industrial Revolution. However, given England's special position as the forerunner of the Industrial Revolution, it is unclear if a transitory post-Malthusian period is a general phenomenon. Using data from Denmark, Norway and Sweden, this research provides evidence for the existence of a post-Malthusian phase in the transition from stagnation to growth in Scandinavia.
Keywords: C32; N3; O1; 330; Demography; Post-Malthusian Dynamics; Malthus; Pre-Industrial Scandinavia; Demographic Transition; Economic Growth